2016
DOI: 10.1080/17470218.2015.1115111
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence on Metacognitive Evaluations: The Power of Nonverbal Cues

Abstract: Metacognitive evaluations refer to the processes by which people assess their own cognitive operations with respect to their current goal. Little is known about whether this process is susceptible to social influence. Here we investigate whether nonverbal social signals spontaneously influence metacognitive evaluations. Participants performed a two-alternative forced-choice task, which was followed by a face randomly gazing towards or away from the response chosen by the participant. Participants then provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Germar, Schlemmer, Krug, Voss, and Mojzisch (2014) showed that in a simple color discrimination task, other people’s responses presented to participants affected their decisions even when they were informed that these decisions came from a completely different task. Similar results with another perceptual decision-making task were obtained by Eskenazi et al (2016). Using the gaze-cueing paradigm, they found that irrelevant gaze directions presented to participants influenced their confidence judgments on the primary task decisions even though the participants were instructed to ignore these stimuli.…”
Section: Social Influencesupporting
confidence: 77%
“…Germar, Schlemmer, Krug, Voss, and Mojzisch (2014) showed that in a simple color discrimination task, other people’s responses presented to participants affected their decisions even when they were informed that these decisions came from a completely different task. Similar results with another perceptual decision-making task were obtained by Eskenazi et al (2016). Using the gaze-cueing paradigm, they found that irrelevant gaze directions presented to participants influenced their confidence judgments on the primary task decisions even though the participants were instructed to ignore these stimuli.…”
Section: Social Influencesupporting
confidence: 77%
“…Exceptions include Karabenick (1996), who found that questions raised by colearners affected participants' judgment of comprehension. Eskenazi et al (2016) found that presenting a face randomly gazing toward or away from the answer chosen by the participants affected confidence in their answers, whereas a car directed similarly to one of the answer options did not affect confidence (see also Jacquot et al, 2015).…”
Section: Social Effects On Metacognitive Processesmentioning
confidence: 98%
“…It has also been shown that social cues within the task might affect individuals’ metacognition [5,6], however, whether social context might impact individuals’ metacognitive processing is, to the best of our knowledge, an open question. We argue that candidates to investigate this question are social contexts involving stereotype threat, i.e.…”
Section: Introductionmentioning
confidence: 99%